Bus drivers who leave: were they more crash-involved? - af Wåhlberg, Anders E.; Dorn, Lisa (Elsevier, 2018)
Turnover is usually considered to be a safety problem for companies, but can also be an advantage, if those who leave are less safe than those who stay. This problem has rarely been investigated for bus drivers, where the financial and human costs of crashes are high. This study tested whether bus drivers who left their jobs had more crashes than those who remained, using company records. Several analyses were run, using crashes per number of days worked, the absolute number of crashes in a specific time period, as well as the ratio of culpable to non-culpable crashes. Drivers who left the company, except those who retired, had forty percent more crashes than those who stayed, but were also less experienced, which explained part of the difference. Results were similar regardless of analysis performed. Turnover may be a problem for bus companies due to the costs of recruitment and training, but this study suggests that there are benefits for turnover too. Fleet-based companies would probably gain more by improving driver selection methods than trying to retain drivers with a high crash rate, as a natural selection process seems to lead to the safest drivers staying with the company.
Keywords: turnover; bus driver; accident; crash